Chitinase-1 inhibition attenuates metabolic dysregulation and restores homeostasis in MASH animal models - Drzewicka, Katarzyna; Głuchowska, Katarzyna M.; Mlącki, Michal; Hofman, Bartłomiej; Tuszyńska, Irina; Ryan, Tristram A. J.; Piwowar, Katarzyna; Wilczyński, Bartosz; Dymkowska, Dorota; Grzybowski, Marcin M.; Dymek, Barbara; Rejczak, Tomasz; et al. (Frontiers in Immunology, 2025)
BackgroundOATD-01 is a chitinase-1 (CHIT1) inhibitor, reducing inflammation and fibrosis in animal models where chronic inflammation leads to tissue remodeling. CHIT1, predominantly secreted by macrophages, is overexpressed in metabolic dysfunction-associated steatohepatitis (MASH).Methods and resultsIn the study, we demonstrated the therapeutic efficacy of OATD-01 in two murine models (STAM, DIAMOND) and one rat model (CDHFD) of MASH. RNA-Seq analysis of livers obtained from CDHFD rat model revealed that OATD-01 reversed MASH-dysregulated genes. In addition to reducing inflammation and fibrosis observed in the rat model, RNA-Seq demonstrated that OATD-01 regulated key metabolic processes such as acetyl-CoA metabolism, triglyceride metabolism, cholesterol synthesis, cholesterol flux, and glycolysis. Using functional assay performed on bone marrow-derived macrophages (BMDMs) we demonstrated that both genetic and pharmacological inactivation of CHIT1 resulted in inhibition of glucose uptake. As a consequence, our data suggest decreased glycolysis, accompanied by increased ATP levels, lower citrate, and increased acetate levels, ultimately leading to a reduced IL-1β secretion in BMDMs.ConclusionsThese results revealed the key role for CHIT1 in regulating metabolism. OATD-01 is a macrophage modulator that can directly restore metabolic balance and consequently inhibit inflammation and fibrosis, supporting its use for MASH treatment.